Digital Talent Transformation: Linking Youth Potential with BUMDes Innovation - Hendrawan, Dimas (Journal of Innovation and Applied Technology, 2026)
This community service program aims to enhance the digital marketing capacity of BUMDes in Tegalweru Village by empowering local youth through training in creative content development using artificial intelligence (AI)-assisted design tools. The program, conducted in collaboration with BUMDes managers and youth organizations, focused on equipping participants with practical skills to create engaging promotional materials and manage Instagram as a primary platform for brand communication. The participatory approach included socialization, focus group discussions, hands-on training, and mentoring. Evaluation results showed significant improvements in participants’ creativity, digital literacy, and ability to independently produce and publish high-quality content on Instagram. The initiative not only increased the visibility and engagement of BUMDes products online but also fostered youth empowerment and sustainable digital transformation in the rural community. It is recommended to replicate this model in other villages to accelerate the adoption of digital marketing and AI-based innovation for rural enterprise development.